Influence of fiber content and applied load on the wear mechanisms of oil palm frond fiber/phenol-formaldehyde composites with functional fillers - Budi Istana; Indra Hasan; Kuntang Winangun (Journal of Engineering Researcher and Lecturer, 2025)
The tribological behavior of oil palm fiber (OPF)-reinforced polymer composites was investigated with varying fiber contents (10, 20, and 30 wt.%) under different applied loads (20, 40, and 60 N) at a sliding speed of 2.5 m/s. Experimental results show that wear rate decreases significantly with increasing fiber content up to 20 wt.% at all loads, reaching minimum values of 1.2, 2.1, and 3.9 ×10-4 mm³/Nm at 20, 40, and 60 N, respectively. Beyond 20 wt.%, wear rate increases, indicating fiber agglomeration and interfacial defects at higher loadings. A second-degree polynomial regression model was developed to predict wear rate as a function of fiber content and load. Model analysis and contour mapping identified an optimum wear resistance region centered at 20 wt.% fiber content and ~35–45 N load. The improved wear performance at this composition is attributed to enhanced fiber–matrix adhesion, improved stress transfer, and reduced microstructural discontinuities. These findings suggest that OPF composites with 20 wt.% reinforcement provide optimal wear resistance under moderate load conditions, making them promising candidates for tribological applications such as automotive and industrial components.